The Analysis of English Test Items Based on Revised Bloom's Taxonomy - Tamelab, Febriana; Kamlasi, Imanuel; Emanuel, Ulu (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2021)
The objectives of this study were to reveal the types of English test items categorized in revised Bloom’s taxonomy and to know the presentation of applying revised Bloom’s taxonomy in the English test. This study applied a qualitative descriptive method to meet the objectives of the study. The English test was documented after getting permission from the English teacher of SMPN 1 Kefamenanu. Then, the English test items were analyzed based on revised Bloom’s cognitive taxonomy. There were six levels of revised Bloom’s cognitive taxonomy namely remembering level, understanding level, applying level, analyzing level, evaluating level, and creating level. The findings showed that there were four out of six levels of revised Bloom’s cognitive taxonomy in that English test. The test had 26 items (52%) for remembering level, 12 items (24%) for understanding level, 5 items (10%) for applying level, and 7 items or 14% for analyzing level. However, there were no items categorized in evaluating level and creating level.